Country Economic Memorandum for Sao Tome and Principe - Background Note 15 : Blue Economy and Environmental Resiliency - de Fountalbert, Charlotte (World Bank, Washington, DC, 2019)
Oceans are an important source of wealth, at least 3 to 5 percent of global GDP is derived from the oceans, but their overall health is reaching a tipping point. Close to a third of fish stocks are fully fished or overfished, climate change is impacting coastal and marine ecosystems through a variety of vectors, unbridled development in the coastal zone is causing erosion, widespread desalination in semi enclosed seas is threatening fauna and flora alike, and marine pollution, particularly from land-based sources is reaching such a proportion that its impacts cannot even be accurately measured. The role of healthy oceans in stabilizing climate and keeping the planet cool is now better understood, and increasingly given the prominence and visibility it deserves in the global action arena. It is also known that business as usual in the different economic sectors associated with coastal and marine ecosystems will have great environmental and social impacts, which are expected to disproportionally affect vulnerable groups of the population, particularly women and girls. This is reflected in Sustainable Development Goal (SDG) 14 - Life Below Water, which calls to conserve and sustainably use the oceans, seas, and marine resources for sustainable development. In this context, the concept of the Blue Economy is particularly relevant and applicable to STP. Different institutions have different definitions of the Blue Economy, which is understood by the Bank as the sustainable and integrated development of oceanic sectors in healthy oceans. There is growing recognition that overfishing, marine pollution, and coastal erosion, among other issues, are pushing oceans to a tipping point to the detriment of the millions who depend on healthy oceans for jobs, nutrition, economic growth, and climate regulation. Central to the Blue Economy approach is the recognition that social benefits should be maximized over the long-term, ensuring that the economic drivers that result from the sustainable use of ocean resources are maintained.